Impact of DMFT, PUFA, DAI, and TDIs on Oral Health-Related Quality of Life (OHRQoL) Among Foundling, Delinquent, and Mainstream School Children: A Prilimenary Study - Alsaif, Abdulaziz Abdullah; Alkhadra, Thamer Adel; AlJameel, AlBandary Hassan (Frontiers in Public Health, 2022)
Objectives To assess oral health and its implication on oral health-related quality of life (OHRQoL) among groups of foundling and delinquent children compared to mainstream children in Riyadh, Saudi Arabia. Materials and Methods This cross-sectional observational study was conducted on children in care houses and mainstream school-going children. The following variables were measured for each group: Demographic data (age, gender); subjective oral health condition; (OHRQoL); clinical oral health condition including the decayed, missing, and filled teeth (DMFT) index; pulpally involved, ulceration, fistula, and abscess (PUFA) index; Dental Aesthetic Index (DAI) for malocclusion, and traumatic dental injuries (TDI). Statistical Analysis A one-way ANOVA test, Chi-square test, and Pearson correlation coefficient were used. Results The total OHRQoL score was significantly higher for the delinquent compared to the mainstream group. In addition, the DMFT and mean PUFA scores were significantly higher for the delinquent group than the others. The DAI revealed statistical significance in occlusion status within the foundling and delinquent groups, and the prevalence of TDI was significantly higher in the delinquent vs. the mainstream group. Conclusion Oral health status appeared to have an association with the OHRQoL among foundling, delinquent, and mainstream children.